The Political Economy of Armaments - Shimshon Bichler; Jonathan Nitzan; Robin Rowley (The Bichler and Nitzan Archives, 1989)
The interaction of oil exports from the Middle East in the 1970s with arms imports to this region has drawn attention from several researchers. The existing literature, however, is seriously flawed for it ignores the large corporate players whose actions synchronize the two flows of income and, thus fails to identify the significance of these corporations for the political economy of armaments. This present paper is the first of a series of four essays that attempt to relate the dynamics of market structures to the escalation of military sales. Here we briefly asses some neo-Marxist and institutional writings that offer insight into the subject of relevant issues. We find them deficient and perhaps outdated in some respects.
Keywords: 330; armament; Baran; corporation; institutionalized waste; Kalecki; Middle East; Macro-Marxism; monopoly capital; oil; surplus; Sweezy; Tsuru; underconsumption; Veblen; Vietnam War